Multiple Cranial Neuropathies and Pachymeningitis in a Patient With a Pathogenic Nucleotide-Binding Oligomerization Domain 2 Polymorphism. Issue 4 (December 2021) - Vegunta, Sravanthi; Bohnsack, John; Crum, Alison; Digre, Kathleen; Katz, Bradley; Seay, Meagan; Quigley, Edward; Kennedy, Sean; Mamalis, Nick; Warner, Judith
Abstract : Abstract: An 11-year-old boy presented with 2 weeks of intermittent headache, right orbital pain, and constant diplopia. Brain MRI showed dural thickening and enhancement of the right lateral cavernous sinus, right orbital apex, and tentorium. Initial cerebral spinal fluid analysis showed only mild pleocytosis, and serum diagnostics were unrevealing. The working diagnosis was Tolosa-Hunt syndrome. His pain and sixth nerve palsy resolved with corticosteroids. Five months after initial presentation, he developed new numbness of the right cheek, complete right ophthalmoplegia, and weakness and numbness of his right hand and leg, all of which were responsive to steroids. Fifteen months later, he returned to the emergency department with 2 weeks of left-sided headaches and acute diplopia. On examination, he had a left cranial nerve 6 palsy. Dural biopsy showed diffuse mononuclear inflammatory cell reaction consisting mostly of lymphocytes with no signs of granuloma formation, nor any epithelioid or giant cells. His clinical course was consistent with an autoinflammatory condition of unknown etiology. Genetic testing with an immunodeficiency panel showed a risk allele in NOD2 (nucleotide-binding oligomerization domain 2) c.3019dup ( p .Leu1007Prof*2) that is associated with an increased risk for Crohn disease. His clinical condition had similarities to central nervous system sarcoidosis. Because of the similarities between our patient's clinical, imaging, and genetic findings and neurosarcoidosis, he was switched to a more targeted therapy—infliximab. His condition has since been stable for nearly 2 years. In conclusion, genetic testing should be considered in patients with suspected occult autoimmunity.